1977
DOI: 10.1113/jphysiol.1977.sp011893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of somatostatin on gastrointestinal function in the conscious and anaesthetized cat and on the isolated cat pancreas.

Abstract: SUMMARY1. Somatostatin, 10 jug kg-1 hr-1, inhibited gastric acid and pepsin secretion stimulated by pentagastrin, 8 ,g kg-1 hr-1, in conscious and anaesthetized cats with chronically implanted gastric fistulae. In the acutely surgically prepared anaesthetized cat, Somatostatin inhibited pepsin secretion but produced little inhibition of gastric acid secretion or mucosal blood flow.2. Secretin stimulated pancreatic juice volume was not significantly reduced in acutely prepared anaesthetized cats, but there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…The mean Ra in the conscious cat is similar to values reported in the anaesthetized cat with vagus and splanchnic nerves sectioned (Reed & Smy, 1971). These results suggest that the significantly lower acid output in response to the same dose of pentagastrin in the anaesthetized compared with the conscious cat (Albinus et al 1977) is unlikely to be the simple result of a limiting MBF in the anaesthetized preparation.…”
Section: Psupporting
confidence: 78%
“…The mean Ra in the conscious cat is similar to values reported in the anaesthetized cat with vagus and splanchnic nerves sectioned (Reed & Smy, 1971). These results suggest that the significantly lower acid output in response to the same dose of pentagastrin in the anaesthetized compared with the conscious cat (Albinus et al 1977) is unlikely to be the simple result of a limiting MBF in the anaesthetized preparation.…”
Section: Psupporting
confidence: 78%
“…It has been reported that the chloralose-anaesthetized acutely surgically prepared cat secretes significantly less acid than the conscious gastric fistula cat in response to pentagastrin 8,ug kg-1 hr-1 (Albinus et al 1977 (Emis & Grossman, 1967). Whether this effect would be marked at the dose of pentagastrin used, which produces acid secretion approaching maximum, is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism whereby the surgical procedures alter the gastric acid response to stimuli requires further investigation. However, it is obvious that care must be taken in interpreting the results from anaesthetized acutely prepared animals, especially in the light of the evidence that somatostatin in the cat (Albinus et al 1977) and atropine in the cat (Blair, Harper, Lake & Reed, 1961;Konturek, Radecki, Demitrescu & I)embinski, 1974) and dog …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that somatostatin does not inhibit enzyme secretion in either isolated arterially perfused preparations or acinic cells in vitro (1,6,23,27,40,41), suggesting that the mechanism of inhibition of pancreatic exocrine secretion is indirect. Indeed, there is evidence that somatostatin is likely to exert the inhibitory effect via a central vagal site (19), the sympathetic nerve (22), an intrapancreatic cholinergic pathway (16), or the intrinsic pancreatic peptidergic neurons (26).…”
mentioning
confidence: 99%